THE FINANCIAL THERMOMETERS OF CREATIVE VILLAGE - Siti Asyraini; Reny Lubis; Sylvia Vianty Ranita (SEAN Institute, 2023)
Financial health through financial thermometers needs to be observed to see the craftsman's ability to manage finances as well as business development. Financial thermometers consist of liquidity ratios, investment ratios, and solvency ratios. This research was conducted on 35 purun craftsmen in Desa Pantai Cermin Kanan, Kabupaten Serdang Bedagai. This research uses a quantitative-descriptive approach. The results of this study found that purun craftsmen in Desa Pantai Cermin Kanan, both those with high and low incomes, had unhealthy liquidity ratios. The liquidity capacity of the craftsmen is 1.79 times for high-income craftsmen and 1.82 times for low-income. The investment ratio, both from the ratio of savings and other investments, obtained information that purun craftsmen who have high and low incomes have good financial health standards of 18% and 28%, respectively. The presence of cooperatives is felt by the community to be quite helpful in developing business capital together. This is in line with the results of research on the calculation of the ratio of the net value of investment assets to the net value of assets, which is 82% when done together.